Basic Counseling and Emotional Regulation Training for Guwosari Village Cadres in Bantul Yogyakarta - Arini Mifti Jayanti; Egi Prawita (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research focuses on addressing challenges in Guwosari Village by enhancing the counselling skills of village cadres and providing emotional regulation training. Method: The research utilized a community service approach to achieve its objectives. It involved training sessions to enhance the counselling skills of Guwosari Village cadres and provided emotional regulation training. Data collection methods included participant observation and pre-and post-training assessments to evaluate the effectiveness of the program. Practical Applications: The study's outcomes benefit Guwosari Village and similar communities, aiding in community development and cadre performance. By enhancing the counselling skills of village cadres, this research contributes to the improvement of community development efforts. Conclusion: This research underscores the significance of equipping village cadres with essential counselling skills and emotional regulation abilities. It has practical implications for community development and the well-being of cadres, ultimately contributing to the betterment of Guwosari Village and similar communities.